The Influence of Compensation and Work Environment on Employee Job Satisfaction at PDAM Luwu Regency - Asma, Nurul; Haedar, Haedar; Dewi, Sari Ratna (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study aims to determine the effect of compensation and work environment on employee job satisfaction in PDAM Luwu Regency. The population of this study were all employees of the Regional Drinking Water Company (PDAM) in Luwu Regency. The sampling technique used is the questionnaire method. Namely all employees of the Luwu District Drinking Water Company (PDAM) office, totaling 40 respondents. This research lasted for 3 days, starting on Monday, December 26, 2022 by filling in a sample questionnaire until Wednesday, December 29, 2022 at the Luwu District Drinking Water Company (PDAM) office. The results of this study indicate that compensation and work environment simultaneously have a significant effect on employee job satisfaction variables in PDAM Luwu Regency. Based on the calculation results of multiple linear regression analysis, it can be seen that the amount of contribution made by compensation and work environment variables to employee job satisfaction at PDAM Luwu Regency simultaneously (R2) is 0.558 or 55.8%, this means that employee performance is 55.8% influenced by compensation and work environment and the remaining 44.2% is influenced by other factors not examined or outside the research model. Partial compensation has no effect on job satisfaction of PDAM Luwu Regency employees, while the work environment partially has a significant effect on job satisfaction of PDAM Luwu Regency employees.